(untitled) (Canadian Medical Education Journal, 2025)
Impression management is the projection of attitudes, beliefs, or actions which are not wholly authentic, to influence perceptions of oneself. This paper describes an autoethnography, conducted in a medical education conference, detailing the process of impression management. The researcher is a PhD student and early-career clinician who wears multiple hats as a student, teacher, and researcher, allowing multiple viewpoints to play into the process of impression management. The autoethnography walks through a process of preparation, impression management, and authenticity which emerged during the observation period, ending with several takeaways to guide further research in this space.